La felicità creativa: in margine alla lettera inedita di Maria Corti ad Antonio Banfi del 17 maggio 1944 (Materiali di Estetica. Terza serie, 2016)
The essay looks at the influence Antonio Banfi and his teachings had over Maria Corti’s early cultural education, especially in the light of the unpublished letter she wrote to her Master in May 1944.